2013
DOI: 10.1364/ol.38.002200
|View full text |Cite
|
Sign up to set email alerts
|

Resonant THz sensor for paper quality monitoring using THz fiber Bragg gratings

Abstract: We report fabrication of THz fiber Bragg gratings (TFBG) using CO 2 laser inscription on subwavelength step-index polymer fibers. A fiber Bragg grating with 48 periods features a ~4 GHz-wide stop band and ~15 dB transmission loss in the middle of a stop band. The potential of such gratings in design of resonant sensor for monitoring of paper quality is demonstrated. Experimental spectral sensitivity of the TFBG-based paper thickness sensor was found to be ~-0.67 GHz / 10 µm. A 3D electromagnetic model of a Bra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Numerous metal- and dielectric-based waveguides234567891011121314151617181920212223242526272829303132333435363738394041424344 and devices, such as fiber Bragg gratings (FBGs)454647 and couplers4849505152535455, have been studied. However, restistive losses of metals and in particular high absorption of most dielectric materials make design of low loss THz waveguides and devices challenging.…”
mentioning
confidence: 99%
“…Numerous metal- and dielectric-based waveguides234567891011121314151617181920212223242526272829303132333435363738394041424344 and devices, such as fiber Bragg gratings (FBGs)454647 and couplers4849505152535455, have been studied. However, restistive losses of metals and in particular high absorption of most dielectric materials make design of low loss THz waveguides and devices challenging.…”
mentioning
confidence: 99%
“…The approach that was developed by us (analysis of the spectral line dynamics) can be used under real conditions together with other THz sensors platforms (for example, [68][69][70][71]) used for the identification and detection of the substance. It might essentially increase a probability of the substance detection.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies demonstrated diagnosing moisture content [186], simultaneous measurements of thickness and moisture [187,188], and multiple parameter determination [189,190,191,192,193]. Aiming at a more compact system, a THz fiber Bragg grating was used to measure paper thickness in [194]. The area was partially reviewed in [195].…”
Section: Paper and Woodmentioning
confidence: 99%